Upaya Mengembangkan Asesmen Keterampilan Pemecahan Masalah Pada Materi Ekosistem Berdasarkan Greenstein - Modok, Sonya Getrida; Dwi Ari Budiretnani; Mumun Nurmilawati; Sulistiono (Universitas Nusantara PGRI Kediri, 2022)
Problem-solving is the basis for identifying problems, making choices, and considering options based on the obtained information. The research objective is to create a problem-solving-based skills assessment instrument based on Greenstein on ecosystem materials. This research uses the Plomp model R&D (Research and Development) development method. The tool uses an expert validation sheet. The study is limited to testing the feasibility of the instrument. Data analysis with percentage technique. The results showed that the assessment instrument for problem-solving skills was feasible with the results of the validation of practitioner experts 86.2%